1007 Obstructive Sleep Apnea (OSA) Is Associated with Longitudinal Increases in Brain Florbetapir PET Imaging, CSF TAU, PTAU, And Decrease in CSF AB42 burden, In Elderly Cognitive Normal (NL) And Mild Cognitive Impairment (MCI) Individuals. (27th April 2018) - BUBU, O M; Umasabor-Bubu, O Q; Sharma, R A; Mukhtar, F; Smith, A H; Mbah, A; Borenstein, A; Mortimer, J; Seixas, A; Jean-Louis, G; Kip, K; Morgan, D; et al.
Abstract: Introduction: Recent studies demonstrate that OSA is associated with Alzheimer's disease (AD) biomarkers. To evaluate evidence for a causal association between OSA and AD, demonstrating AD-specific neuropathology changes resulting from increased disease burden in OSA patients is vital. We determined the effect of OSA on longitudinal changes in AD biomarkers in NL, MCI and AD older adults. Methods: Participants included 516 NL, 798 MCI and 325 AD subjects from the Alzheimer's disease Neuroimaging Initiative (ADNI). Participant self-reported physician diagnosis of OSA. Serial brain Aβ42, CSF-TAU, PTAU, and CSF-Aβ42 burden were determined. Multi-level mixed effects linear regression models with randomly varying intercepts and slopes were constructed to test whether the rate of change in biomarker data differed between subjects with and without OSA. The final models were adjusted for age, sex, BMI, CPAP use, APOE-e4 status, and history of chronic medical conditions. Results: Mean ages for OSA+ and OSA- patients were 72.3 ± 7.1 and 73.9 ± 7.3 respectively. Mean follow-up time was 2.52 ± 0.51 years. In NL and MCI groups, the annual rate of AD biomarker burden change over time, indicated that OSA+ subjects experienced faster increase in brain Aβ-42 (B = - .06, 95% CI, -.09, -.04 for both), CSF-TAU (B = -2.89, 95% CI, -3.51 to -2.29 and B = -1.89, 95% CI, -2.91, -.87, respectively), CSF-PTAU (B = -1.21, 95% CI, -1.71, -.74 and, B = -1.48, 95% CI, -2.05, -.94, respectively), and a faster decrease in CSF-Aβ-42 (B = 3.93, 95% CI, 3.56, 4.31 and B = 2.69, 95% CI, 2.02, 3.36, respectively); compared to OSA- subjects, over the follow-up period. Conclusion: OSA appears to accelerate increases in brain amyloid, CSF TAU and PTAU burden, and decreases in CSF AB42 burden, over time, both in elderly Cognitive Normal and MCI individuals. Clinical interventions aimed at OSA, in these populations, could possibly slow the progression of cognitive impairment to AD Support (If Any): None.